Functionalized Periodic Mesoporous Silica Nanoparticles for Inhibiting the Progression of Atherosclerosis by Targeting Low-Density Lipoprotein Cholesterol - Hao Jin; Wenbin Lu; Yahao Zhang; Yong Wu; Jiandong Ding; I. R. Chiara Villamil Orion; Cihui Liu (MDPI AG, 2024)
Atherosclerotic disease is a substantial global burden, and existing treatments, such as statins, are recommended to lower low-density lipoprotein cholesterol (LDL-C) levels and inhibit the progression of atherosclerosis. However, side effects, including gastrointestinal unease, potential harm to the liver, and discomfort in the muscles, might be observed. In this study, we propose a novel method using periodic mesoporous silica nanoparticles (PMS) to create heparin-modified PMS (PMS-HP) with excellent biocompatibility, enabling selective removal of LDL-C from the blood. In vitro, through the introduction of PMS-HP into the plasma of mice, we observed that, compared to PMS alone, PMS-HP could selectively adsorb LDL-C while avoiding interference with valuable components such as plasma proteins and high-density lipoprotein cholesterol (HDL-C). Notably, further investigations revealed that the adsorption of LDL-C by PMS-HP could be well-fitted to quasi-first-order (R2 = 0.993) and quasi-second-order adsorption models (R2 = 0.998). Likewise, in vivo, intravenous injection of PMS-HP enabled targeted LDL-C adsorption (6.5 ± 0.73 vs. 8.6 ± 0.76 mM, p < 0.001) without affecting other plasma constituents, contributing to reducing intravascular plaque formation (3.66% ± 1.06% vs. 1.87% ± 0.79%, p < 0.05) on the aortic wall and inhibiting vascular remodeling (27.2% ± 6.55% vs. 38.3% ± 1.99%, p < 0.05). Compared to existing lipid adsorption techniques, PMS-HP exhibited superior biocompatibility and recyclability, rendering it valuable for both in vivo and in vitro applications.